A Case of an Incidentally Removed Lingual Osseous Choristoma - Tomotaka Hemmi; Jun Suzuki; Satoko Sato; Masumi Tabata; Kojiro Watanabe; Mitsuru Sugawara; Yukio Katori (Case Reports in Otolaryngology)
Lingual osseous choristoma is a rare benign tumor consisting of normal matured bone tissue. It was first reported in 1913, and less than 100 cases of lingual osseous choristomas, mainly in their twenties and thirties, have been reported in the English literature until now. Here, we report an additional case of lingual osseous choristoma, in an elderly patient, that was incidentally removed by coughing and cured without additional interventions. An 89-year-old male patient was referred to our department for an evaluation of chronic cough. When we examined his oral cavity and pharynx, he expectorated a 10 -mm mass which was histologically diagnosed as an osseous choristoma. We confirmed the well-defined, rounded, high-density mass with a tiny pedicle on the base of the tongue in previous cervical spine CT images. No signs of recurrence were found during the 15-month follow-up examination. Our case serves as a reminder of this rare entity in the diagnosis of tongue masses of the elderly.